2017
DOI: 10.1017/s1431927617000010
|View full text |Cite
|
Sign up to set email alerts
|

Oral Function Improves Interfacial Integrity and Sealing Ability Between Conventional Glass Ionomer Cements and Dentin

Abstract: The aim was to investigate if load cycling affects interfacial integrity of glass-ionomer cements bonded to sound or caries-affected dentin. A conventional glass-ionomer, Ketac Bond and a resin-modified glass-ionomer, (Vitrebond Plus), were applied to dentin. Half of the specimens were load cycled. The interfaces were submitted to dye assisted confocal microscopy evaluation. The unloaded specimens of sound and carious dentin were deficiently hybridized when Ketac Bond was used. Ketac Bond samples showed an abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Nevertheless, the current study showed a slight, but nonsignificant increase of bond strength values along with reduction of interfacial nanoleakage, in those specimens created with application of the RMGIC on BAG air-abraded dentine. It is believed that load cycling may have contributed to enhance the bioactive synergic effect of BAG and the RMGIC, which protected and remineralised the bonded-dentine interface due to mineral crystallites remaining within the collagen after partial demineralisation, acting as seed sites for apatite growth 48,49 . Indeed, Toledano at al., 33 showed that mechanical loading may promote dentine mineralisation at 24h and 21 days of storage in distilled water, with increase of the mineral-matrix ratio, lack of nanoleakage and permeability at the resin-dentine interface of specimens created through self-etching and EDTAconditioned bonding approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the current study showed a slight, but nonsignificant increase of bond strength values along with reduction of interfacial nanoleakage, in those specimens created with application of the RMGIC on BAG air-abraded dentine. It is believed that load cycling may have contributed to enhance the bioactive synergic effect of BAG and the RMGIC, which protected and remineralised the bonded-dentine interface due to mineral crystallites remaining within the collagen after partial demineralisation, acting as seed sites for apatite growth 48,49 . Indeed, Toledano at al., 33 showed that mechanical loading may promote dentine mineralisation at 24h and 21 days of storage in distilled water, with increase of the mineral-matrix ratio, lack of nanoleakage and permeability at the resin-dentine interface of specimens created through self-etching and EDTAconditioned bonding approaches.…”
Section: Discussionmentioning
confidence: 99%
“…It comprises an intermediate layer between the GIC and the tooth substrate. In 10 studies that showed this interphase layer, the time for the formation was 1 to 10 days of contact between GIC and tooth substrates [44,45,55,62,67,68,71,72,75,76]. It develops due to chemical interaction between the filling and tooth.…”
Section: Gic-tooth Interaction Interphasementioning
confidence: 99%
“…Five of them used Yes (6) Yes, No (7) C, M (8) No fluorescence staining with rhodamine B [44,45,68,69,72], and two of them used time lapse imaging to observe cement luting, dehydration, and rehydration [58,73]. Two reports from the same research group looked at the effects of mechanical loading on the GIC-dentine attachment [45,72]. Sidhu et al [69] used real-time imaging of a shear test to examine GIC failure modes, which was 100% cohesive.…”
Section: Nomentioning
confidence: 99%
See 2 more Smart Citations